2016
DOI: 10.1017/dmp.2016.165
|View full text |Cite
|
Sign up to set email alerts
|

Children in the Syrian Civil War: the Familial, Educational, and Public Health Impact of Ongoing Violence

Abstract: Objective: The Syrian civil war since 2011 has led to one of the most complex humanitarian emergencies in history. The objective of this study was to document the impact of the conflict on the familial, educational, and public health state of Syrian children. Methods: A cross-sectional observational study was conducted in May 2015. Health care workers visited families with a prospectively designed data sheet in 4 Northern Syrian governorates. Results: The 1001 children included in this study originated from Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
2
28
1
1
Order By: Relevance
“…Due to the severity and complexity of the armed con ict, Syria has shifted from a temporary to a permanent country of origin of refugees. This results in a continuously decreasing health status of Syrian citizens as also demonstrated that by a recent study in which only 64% had access to general pediatric care, 28% had up-to-date vaccination status and 16% access to healthy nutrition [23]. The Syrian context is contrasted by Afghanistan, which has been one of the top 20 countries of origin of refugees since the 1980s [1].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the severity and complexity of the armed con ict, Syria has shifted from a temporary to a permanent country of origin of refugees. This results in a continuously decreasing health status of Syrian citizens as also demonstrated that by a recent study in which only 64% had access to general pediatric care, 28% had up-to-date vaccination status and 16% access to healthy nutrition [23]. The Syrian context is contrasted by Afghanistan, which has been one of the top 20 countries of origin of refugees since the 1980s [1].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the severity and complexity of the armed conflict, Syria has shifted from a temporary to a permanent country of origin of refugees. This results in a continuously decreasing health status of Syrian citizens as also demonstrated that by a recent study in which only 64% had access to general pediatric care, 28% had up-to-date vaccination status and 16% access to healthy nutrition (21). The Syrian context is contrasted by Afghanistan, which has been one of the top 20 countries of origin of refugees since the 1980s(1).…”
Section: Discussionmentioning
confidence: 99%
“…Ortalama 6 yaşında olan bu çocukların kendi yaşam alanları dı-şında yerlerde yaşadıkları, ailelerinin kayıp olduğu, temiz suya ulaşamadıkları, uygun temizlik, beslenme ve sağlık-bakım hizmetleri alamadıkları, büyük çoğunluğunun aşılanamadığı ve yarısından fazlasının eğitime ulaşamayan okul çağı çocukları oldukları belirtilmiştir. 12 Çocuk olmanın getirdiği rollerin fakına varamadan dünyanın başka bir yüzü ile karşı karşıya kalan çocuklar, aileleri ile girmek zorunda kaldık-ları mücadelede en masum ama bir o kadar da en sıkıntılı durumları yaşamak zorunda kalan grup olmuştur. Uzun ve yorucu yolculuklara dayanamayan, beklenenin aksine küçücük bedeni ve ruhu en ağır yaraları almıştır.…”
Section: Türki̇ye'deki̇ Mülteci̇leri̇n Sağlik Eği̇ti̇m Haklari Ve Karşilaşunclassified